Notes on Perlodinella Klapálek, 1912 (Plecoptera: Perlodidae) with a new species and a new synonym - Huo, Qing-Bo; Du, Yu-Zhou; Zwick, Peter; Murányi, Dávid (Zootaxa, 2022)
After reexamining the syntype series of Perlodinella kozlovi Klapálek, 1912, a new species of Perlodinella, P. tibetensis Huo & Du sp. nov. is proposed, and a lectotype is designated for P. kozlovi. Another monotypic genus of Perlodidae, Rauserodes Zwick (1999), is considered as a synonym of Perlodinella in this paper.